Examining Critical Junctures in Macroeconomic Policy in Nondemocratic States: Algeria and Jordan in Comparative Perspective. (16th April 2013) - Hogan, John; Cavatorta, Francesco
Abstract The article uses the critical junctures framework in examining changes in macroeconomic policy in Algeria and Jordan during the late 1980s to determine if these policy changes constituted critical junctures. Both cases are significantly different from those studied previously using the framework, as neither state was a liberal democracy. The absence of democracy, and as a consequence of accountability, is a factor with which the critical junctures framework has not previously had to contend. This study will also enable us determine if the framework is sufficiently robust to be applied to the examination of macroeconomic policy changes in nondemocratic states. The findings show that in both countries political liberalization did not follow upon economic liberalization, giving lie to the often expressed assumption that economic liberalization and democratization go hand in hand. Instead, as the ruling elites in both countries sought to revive their economies, while maintaining their own positions in society, economic policy reforms required a gesture toward democratization but little else.